RNA Polymerase Sigma Factor That Blocks Morphological Differentiation by Streptomyces coelicolor - Gehring, Amy M. (American Society for Microbiology, 2001)
The filamentous bacterium Streptomyces coelicolor undergoes a complicated process of morphological differentiation that begins with the formation of an aerial mycelium and culminates in sporulation. Genes required for the initiation of aerial mycelium formation have been termed bld (bald), describing the smooth, undifferentiated colonies of mutant strains. By using an insertional mutagenesis protocol that relies on in vitro transposition, we have isolated a bld mutant harboring an insertion in a previously uncharacterized gene, SCE59.12c, renamed here rsuA. The insertion mutant exhibited no measurable growth defect but failed to produce an aerial mycelium and showed a significant delay in the production of the polyketide antibiotic actinorhodin. The rsuA gene encodes an apparent anti-sigma factor and is located immediately downstream of SCE59.13c, renamed here sigU, whose product is inferred to be a member of the extracytoplasmic function subfamily of RNA polymerase sigma factors. The absence of rsuA in a strain that contained sigU caused a block in development, and the overexpression of sigU in an otherwise wild-type strain caused a delay in aerial mycelium formation. However, a strain in which both rsuA and sigU had been deleted was able to undergo morphological differentiation normally. We conclude that the rsuA-encoded anti-sigma factor is responsible for antagonizing the function of the sigma factor encoded by sigU. We also conclude that the sigU-encoded sigma factor is not normally required for development but that its uncontrolled activity obstructs morphological differentiation at an early stage.